2017
DOI: 10.3354/meps12001
|View full text |Cite
|
Sign up to set email alerts
|

Biological mechanisms of marine invasions

Abstract: Table S1: Search parameters used in ISI Web of Science. General search terms used for all mechanisms were (non-native* OR nonnative* OR invasi* OR introduc* OR non-indigenous OR nonindigenous OR alien OR exotic OR invade*) AND (estuar* OR marine OR coastal OR ocean* OR sea OR *tidal), followed by mechanism-specific terms outlined below. Search results were then refined using Web of Science tools to those pertaining only to Marine and Freshwater Biology, and all research areas that were clearly not relevant (e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 164 publications
1
60
0
Order By: Relevance
“…Further evaluation of combined indirect and direct effects of competitors and consumers on populations of NIS via interactions throughout complex natural trophic webs is needed (Papacostas et al . ). Furthermore, few studies have examined the cascading effects of marine management strategies on invasions, despite promises of increased resilience in ‘healthier’ well‐managed ecosystems (Burfeind et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Further evaluation of combined indirect and direct effects of competitors and consumers on populations of NIS via interactions throughout complex natural trophic webs is needed (Papacostas et al . ). Furthermore, few studies have examined the cascading effects of marine management strategies on invasions, despite promises of increased resilience in ‘healthier’ well‐managed ecosystems (Burfeind et al .…”
Section: Introductionmentioning
confidence: 97%
“…Papacostas et al . () found that among studies describing negative interactions (comprising the majority of studies in the analysis), most showed an increase in invasion success with release from competitors and consumers (i.e. biotic resistance), but among those, predation was found to limit invasion success more often than competition.…”
Section: Introductionmentioning
confidence: 99%
“…Ultimately, the absence of co‐occurrence‐linked mortality suggests that both species could co‐exist and suggests that weaker competitive interactions prevail in this system, which prevent the total exclusion of native or invasive species (Papacostas et al, ). This would suggest that the presence of M. gigas would only affect the recovery of native oyster populations under specific environmental context (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…, Saul and Jeschke ), but the relative importance of biotic mechanisms in this process is context dependent (e.g., terrestrial and marine systems; Papacostas et al. ), making it difficult to identify generalities (but see Hui and Richardson ). In addition, the introduction of some species can modify the receiving environment, making it more suitable for further invasions through positive feedbacks (Gaertner et al.…”
Section: Third Component: Mechanistic Understanding Of the Spread Of mentioning
confidence: 99%
“…Alien species can modify species interactions (Papacostas et al. ) or the environment (Bax et al. ) in ways that might only lead to loss of biodiversity in the future (Essl et al.…”
Section: Fourth Component: Mechanistic Understanding Of the Impact Ofmentioning
confidence: 99%